2011
DOI: 10.1016/j.burns.2010.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of maximal aerobic capacity in severely burned children

Abstract: Introduction-Maximal oxygen uptake (VO 2 peak) is an indicator of cardiorespiratory fitness, but requires expensive equipment and a relatively high technical skill level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…20,2325 In burn patients, aerobic capacity is severely affected and remains below normal values despite significant improvements obtained through aerobic exercise. 5,24,26 According to a recent study, peak VO 2 has a “tendency to plateau or deteriorate” in burned adults.…”
Section: Discussionmentioning
confidence: 99%
“…20,2325 In burn patients, aerobic capacity is severely affected and remains below normal values despite significant improvements obtained through aerobic exercise. 5,24,26 According to a recent study, peak VO 2 has a “tendency to plateau or deteriorate” in burned adults.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that participation in exercise activities has beneficial effects in the rehabilitation of burned children. Improvements in the range of joint movement (4), lean body mass (LBM), muscle strength, aerobic capacity, and average muscle power are seen in burned children after completion of 12 weeks of exercise training (57). However, exercise does not reduce metabolic rate in burned children (8).…”
mentioning
confidence: 99%
“…Measured VO 2 max, as assessed using the Ultima CardiO2 System, was compared with predicted values obtained using the Cooper, Bruce, American College of Sports Medicine (ACSM), and Porro [13] formulas. The Cooper formula was as follows: VO 2 (mL/min) = 43.6 × height (cm) − 4547.1 for males and VO 2 (mL/min) = 22.5 × height (cm) − 1837.8 for females.…”
Section: Methodsmentioning
confidence: 99%
“…We used this formula since most, if not all of our patients, were unable to run. Porro and coworkers developed a formula for severely burned children at 6 months after discharge from the burn intensive care unit [13]. VO 2 max = 10.33 − 0.62 × age (years) + 1.88 × treadmill time (min) + 2.3 (sex; females = 0, males = 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation